IMF Committee on Balance of Payments Statistics : Annual Report 2021. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
The 2021 Annual Report1 of the IMF Committee on Balance of Payments Statistics (the Committee) provides an overview of recent trends in global balance of payments and international investment position statistics, on this occasion with special emphasis on the significant effects of the pandemic on selected balance of payments components, particularly cross-border trade, tourism, and financial flows. The Report also summarizes the Committee's work and presents the work program for the coming year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; Investment Decisions; Portfolio Choice; Dominica